2004
DOI: 10.1557/jmr.2004.19.3.752
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Structure of Calcium Silicate Intergranular Films Between Prism and Basal Planes in Silicon Nitride: A Molecular Dynamics Study

Abstract: Molecular dynamics simulations of approximately 15 Å thick intergranular films (IGFs) containing SiO 2 and CaO in contact with two surface terminations of the prism (1010) and basal planes (0001) of Si 3 N 4 were performed using a multibody interatomic potential. Samples with the same composition (1.5 mol% CaO) and number of atoms but different crystal planes (i.e., the prism and basal planes of Si 3 N 4 ) were studied. In both the prism and basal cases, the IGF in the final configuration is well-ordered in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 24 publications
4
34
1
Order By: Relevance
“…The snapshot of atomistic structure uses only a thin slice of the actual system perpendicular to the plane of the figure to enable better visualization of the structure and bonding. Compared to previous studies of IGF's in contact with ideal ␤ -Si 3 N 4 crystal surfaces, 30,31 atoms in the IGF are less ordered in the interface region. This is shown with more detail in Fig.…”
Section: Model Constructioncontrasting
confidence: 76%
See 2 more Smart Citations
“…The snapshot of atomistic structure uses only a thin slice of the actual system perpendicular to the plane of the figure to enable better visualization of the structure and bonding. Compared to previous studies of IGF's in contact with ideal ␤ -Si 3 N 4 crystal surfaces, 30,31 atoms in the IGF are less ordered in the interface region. This is shown with more detail in Fig.…”
Section: Model Constructioncontrasting
confidence: 76%
“…Periodic boundary conditions were applied in the x, y, and z directions. Table III shows the previously discussed 31,32 heat and quench process used in the simulations. All atoms in the Si 3 N 4 crystal were immobilized from 10 000 K to 4000 K while the atoms in the IGF went through the melt-quench process to form the amorphous IGF.…”
Section: Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should have significant implications in the kinetic behavior of these systems during sintering and local compositional changes or particle rearrangements. We also observed strained siloxane bonds at the IGF/crystal interfaces, with less strain farther from the interface 1,2 . Results of Si-O bond lengths are consistent with the newest pair distribution functions found experimentally for the 1nm IGFs between silicon nitride crystals 4 .…”
mentioning
confidence: 60%
“…Interestingly, in the case of the IGF between β-Si 3 N 4 crystals, the MD simulations showed that growth of the basal plane in the <0001> direction is more likely than growth along the < 101 0 > direction 1,2 . Hence, the results of our simulations imply different types of crystal growth for the two systems studied: preferential growth along the prism plane normal in the alumina case, but preferential growth along the basal plane normal in the nitride case.…”
mentioning
confidence: 99%